Selected results of growth acceleration in East Germany - Jaeger, U.; Kromeyer-Hauschild, Katrin; Zellner, K. (1990)
Anthropometric surveys have been conducted in the city of Jena since 1880. Therefore, it is possible to document secular changes in growth and maturation occurring in a single community over the period of 110 years. Changes in the health status and quality of nutrition of that period have produced increases in stature and body weight of all age categories. In addition, decreases in infant mortality and life expectancy have been recorded. Although adult body size has increased, much of the increase recorded at earlier ages can be attributed to acceleration of the growth process with a given value being attained at an earlier chronological age throughout the growth process. Also, a well-documented acceleration of the onset of menarche has brought the average age for that event down to 12.5 years in 1985 as compared to 15.49 in the past century
Conference "Anthropology and health: demography and physiology of aging", Dubrovnik, 12-19.8.1990.
Bibliografija: 9 jed.
Keywords: Tjelesna težina; Tjelesna visina; Njemačka -- Jena